2016
DOI: 10.1111/jphp.12495
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of tenofovir or emtricitabine to pregnant rats; effect on Abcb1a, Abcb1b and Abcg2 expression in the placenta and in maternal and fetal organs

Abstract: Our data broaden current knowledge on safety profile of tenofovir and emtricitabine use in pregnancy. Nevertheless, further research in other mammal species, including humans, is important to fully elucidate this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…PCR was performed using the TaqMan Universal Master Mix II without uracil-DNA glycosylase (Thermo Fisher Scientific) and predesigned TaqMan Real Time Expression PCR assays for human (h) or rat (r) SLC29A1 (Hs01085704_g1c, Rn01648953_m1) and SLC29A2 (Hs00155426_m1, Rn01479421_m1). For greater precision during the mRNA quantification of 1818 Cerveny et al target genes, data were normalized against the geometric mean of expression of two previously identified TaqMan housekeeping genes: B2M (Hs00187842_m1) and GAPDH (Hs02758991_g1) for human samples, and Ywhaz (Rn00755072_m1) and Gapdh (Rn01775763_g1) for rat samples Cerveny et al, 2016). Stable expression of both reference genes was verified before beginning the quantitative analysis.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed using the TaqMan Universal Master Mix II without uracil-DNA glycosylase (Thermo Fisher Scientific) and predesigned TaqMan Real Time Expression PCR assays for human (h) or rat (r) SLC29A1 (Hs01085704_g1c, Rn01648953_m1) and SLC29A2 (Hs00155426_m1, Rn01479421_m1). For greater precision during the mRNA quantification of 1818 Cerveny et al target genes, data were normalized against the geometric mean of expression of two previously identified TaqMan housekeeping genes: B2M (Hs00187842_m1) and GAPDH (Hs02758991_g1) for human samples, and Ywhaz (Rn00755072_m1) and Gapdh (Rn01775763_g1) for rat samples Cerveny et al, 2016). Stable expression of both reference genes was verified before beginning the quantitative analysis.…”
Section: Methodsmentioning
confidence: 99%
“…While Mdr1a expression was higher in maternal vs. fetal organs, the expression of Bcrp was comparable in both the organs. The expression of Mdr1b was higher in some maternal organs than the fetal organs (296). Petrovic et al , observed a time dependent decrease in the levels of mRNA of Bcrp 24 h post-treatment with endotoxin in rats.…”
Section: Recent Findings From Studies Involving Multiple Abc Transmentioning
confidence: 99%
“…For example, neurotoxicity observed in cases of neonatal hyperbilirubinemia, linked to atazanavir (ATV) exposure, displays sex differences in occurrence, raising questions regarding ATV interactions with bilirubin transporters and metabolic enzymes in the fetal and neonatal liver [31,32]. To date, limited research has focussed on understanding the expression of transporters and metabolic enzymes in the fetal brain and liver as well as placenta in the context of ART [33,34], with little consideration of fetal sex as a variable. Lamivudine (3TC), abacavir (ABC), ATV, and ritonavir (RTV) constitute an ART regimen (3TC/ABCþATV/r) used in pregnancy, with each of these drugs also recommended by the WHO as part of other first-line and second-line regimens [35].…”
Section: Introductionmentioning
confidence: 99%